Arahan Perencanaan Tapak pemakaman Srengseng Sawah - Linda Wardani; Weishaguna; Fachmy Sugih Pradifta (UNISBA Press, 2023)
Abstract. This study aims to provide guidance regarding the Srengseng Sawah cemetery site. The background of this study is the lack of clear guidance on the cemetery site in Srengseng Sawah. This research uses a Mixed Methods approach with data collection techniques through interviews, field observations, and literature studies. The results of this study will produce recommendation guidance in the form of zoning and cemetery structures that are in line with local cultural characteristics and sustainability. Zoning will consider aspects such as land availability, layout, and spatial structure. The cemetery structure will consider the theory of neighborhood, which takes into account the distance, functional importance of each facility, and the layout of facilities. It is expected that the results of this study can contribute to the development of sustainable cemetery sites in Srengseng Sawah. The generated recommendation guidance can serve as a guideline for the government, relevant stakeholders, and the community in planning and managing cemetery sites in Srengseng Sawah. Additionally, this research can also serve as a reference for further research in the fields of urban planning, architecture, and cemetery planning Abstrak. Studi ini bertujuan untuk memberikan arahan terkait tapak pemakaman Srengseng Sawah. Latar belakang studi ini adalah belum adanya arahan yang jelas terkait tapak pemakaman di Srengseng Sawah. Penelitian ini menggunakan pendekatan Mix Methode dengan teknik pengumpulan data melalui wawancara, observasi lapangan, dan studi literatur. Hasil penelitian ini akan menghasilkan rekomendasi arahan berupa zonasi dan struktur pemakaman yang sesuai dengan karakteristik budaya setempat dan berkelanjutan. Zonasi akan mempertimbangkan aspek-aspek seperti ketersediaan lahan, tata letak dan struktur ruang. Struktur pemakaman akan mempertimbangkan teori neighbourhood yang mempertimbangkan jarak, kepentingan fungsi setiap fasilitas dan tata letak fasilitas. Diharapkan hasil studi ini dapat memberikan kontribusi dalam pengembangan tapak pemakaman yang berkelanjutan di Srengseng sawah Rekomendasi arahan yang dihasilkan dapat menjadi pedoman bagi pemerintah, pemangku kepentingan terkait, dan masyarakat dalam merencanakan dan mengelola tapak pemakaman di Srengseng Sawah. Selain itu, penelitian ini juga dapat menjadi referensi bagi penelitian selanjutnya dalam bidang perencanaan perkotaan, arsitektur dan perencanaan pemakaman.